An exploration of teacher's use of iPads for students with learning support needs. Issue 2 (14th August 2017) - Chambers, Dianne; Jones, Phyllis; McGhie‐Richmond, Donna; Riley, Michael; May‐Poole, Sarah; Orlando, Ann Marie; Simsek, Orhan; Wilcox, Catherine
Abstract : This project explored how iPads were being used in a range of K‐12 schools to support the learning of students with a range of learning support needs. Groups of teachers (and other professionals) from the USA, Canada, Australia and the UK were invited to complete an online survey focused on the use of iPads in their classrooms, perspectives of their skill level, and how their school and school districts support the use of iPads. The survey focused on iPad use in classrooms (curriculum and skills); teachers' skill levels; whether iPads are addressed in the Individualised Education Program (IEP); the systemic support for the iPads; and the perceived benefits and barriers. The results reveal that respondents are using iPads across many areas of the curriculum, which affirms the research in the emerging literature base. However, there are teacher reported differences in the manner and scope of iPad use in the classrooms and also the integration of the iPad in the IEP. The research also highlights variability in reported skill level for the iPad and an increased need for enhanced systemic support, such as training, funding, technical support and administrative support for the use of the iPad as a pedagogical tool.